Synthesis of a Ribose-Incorporating Medium Ring Scaffold via a Challenging Ring-Closing Metathesis Reaction - Rankin, Stuart S.; Caldwell, John J.; Cronin, Nora B.; van Montfort, Rob L. M.; Collins, Ian (European journal of organic chemistry, 2016)
A practical synthesis of a novel oxabicyclo[6.2.1]undecenetriol useful as a medicinal chemistry scaffold has been developed starting from l‐ribose. The sequence involves an oxidation/Grignard addition sequence and a challenging ring‐closing metathesis (RCM) reaction as the ring forming step. Exploration of the RCM substrate protecting groups revealed the key factor for successful nine‐membered medium ring formation to be conformational bias of the reacting alkenes of the RCM substrate by very bulky silyl ether protecting groups. The synthesis also allowed access to an epimeric triol and saturated and unsaturated variants of the nine‐membered ring. The medium ring conformation of the oxabicyclo[6.2.1]undecenetriol was determined by X‐ray crystallography and correlated to the solution state conformation by NMR experiments. A practical synthesis of a novel oxabicyclo[6.2.1]undecenetriol has been developed, via a challenging ring‐closing metathesis (RCM) reaction. The key factor for successful medium ring formation was the use of bulky silyl ether protecting groups. X‐ray crystallography of the triol and NMR experiments revealed a well‐defined medium ring conformation.